Regenerated Oxidized Cellulose as a Sealant and Adhesive in Endoscopic Endonasal Skull Base Reconstruction - Ashwin Gajendran Vedhapoodi; Aravind Sabesan; Benazir Ferozkhan; Saravana Selvan Velmurugan; Venkatesan Rajarajan; Baskar Arukavur Radhakrishnan; Kanagaraman Prabhuraman; Bhuvaneswari Natarajan (International Archives of Otorhinolaryngology)
Introduction An ideal and long-lasting adhesive and sealant is essential during endoscopic endonasal skull-base surgery to hold the reconstruction intact and prevent cerebrospinal fluid (CSF) permeation until complete healing occurs. Fibrin glue is the most common material used. Regenerated oxidized cellulose (ROC) has not been mentioned in the literature as sealant and adhesive, and, hence, we intended to study this role.